Research assistants’ perception of mistreatment and the strategies they prefer to overcome this mistreatment - Günçavdı, Gizem; Polat, Soner (Journal of Human Sciences, 2015)
The purpose of this study is to determine research assistants’ perception of mistreatment from other faculty members and the strategies they prefer to overcome this mistreatment. The sample of this study includes 255 research assistants who work at seven faculties at Kocaeli University, Turkey. This study is in the descriptive survey model. In order to measure research assistants’ perception of mistreatment, “Mistreatment Scale” developed by Harlos and Axelrod (2005) and adapted to Turkish by Günçavdı and Polat (2015); and in order to measure strategies which research assistants prefer to overcome this mistreatment, “Secondary Appraisal Scale” developed by Rogers (1998) were used as data collection tools. It has been found out that research assistants’ perception of mistreatment from faculty showed significant difference depending on personal and organizational variables. Also it has been found out that research assistants used “barriers” strategies mostly to overcome mistreatment. This research has given an idea about research assistants’ experiences about being exposed to mistreatment, but this study is limited to students at Kocaeli University. In the future researches, the samples can be extended by taking research assistants who work at other universities as the sample.